Phenomenology of men with body dysmorphic disorder concerning penis size compared to men anxious about their penis size and to men without concerns: A cohort study. (March 2015) - Veale, David; Miles, Sarah; Read, Julie; Troglia, Andrea; Carmona, Lina; Fiorito, Chiara; Wells, Hannah; Wylie, Kevan; Muir, Gordon
Highlights: Men with body dysmorphic disorder (BDD) can be differentiated from men with and without small penis anxiety (SPA). Men with BDD experience higher symptoms of psychopathology. Men with BDD avoid more anxiety provoking situations and employ more safety-seeking behaviours as compared to men with and without SPA. Men with BDD experience more recurrent imagery. Abstract: Men with body dysmorphic disorder (BDD) may be preoccupied with the size or shape of the penis, which may be causing significant shame or impairment. Little is known about the characteristics and phenomenology of such men and whether they can be differentiated from men with small penis anxiety (SPA) (who do not have BDD), and men with no penile concerns. Twenty-six men with BDD, 31 men with SPA, and 33 men without penile concerns were compared on psychopathology, experiences of recurrent imagery, avoidance and safety-seeking behaviours. Men with BDD had significantly higher scores than both the SPA group and no penile concern group for measures of imagery, avoidance, safety seeking and general psychopathology. The groups differed on the phenomenology of BDD specific to penile size preoccupation clearly from the worries of SPA, which in turn were different to those of the men without concerns. The common avoidance and safety seeking behaviours were identified in such men that may be used clinically.